KOMUNIKASI ORGANISASI DI SMK - Elia Susilawati (UNIVERSITAS BENGKULU, 2016)
The objective of this study is to describe the organizational communication of Vocational Hidgh School. This study uses a descriptive-qualitative method and uses interview, observation and documentation. The main subjects of the study were teachers, headmaster, administrative staff, students of State Agricultural Vocational School Number Two of Tugumulyo.??The findings of the study were (1) the organizational communication was understood as tool to inform; (2) the communication were mostly based on the cultural and human relationship; (3) external communication was done by cooperating and internal communication was built intensively; (4); kinds of communication tools used were traditional and modern ones.; (5) there is problem in communication.Keyword: organization, communication, school, vocational